1996
DOI: 10.1111/j.1432-1033.1996.0675w.x
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus nidulans Penicillin‐Biosynthesis Gene aat (penDE) is Controlled by a CCAAT‐Containing DNA Element

Abstract: Analysis of the promoter of the penicillin biosynthesis nut (penDE) gene of Aspergillus niduluns using band-shift assays led to the identification of a CCAAT-containing DNA element which was specifically bound by a protein (complex). The identified DNA element was localised about 250 bp upstream of the transcriptional-start sites of uat: Substitution of the CCAAT core sequence by GATCC led to a fourfold reduction of expression of an aat-1acZ gene fusion. The identified binding site thus was functional in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…PENR1 positively regulates the expression of two penicillin biosynthetic genes, ipnA and aatA. Deletion of hapB, hapC, and hapE genes, which encode PENR1 complex components, resulted in identical phenotypes characterized by low levels of ipnA and aatA expression as well as a slow-growth phenotype and a reduction in conidiation (74,87,112).…”
Section: Ccaat Binding Protein Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…PENR1 positively regulates the expression of two penicillin biosynthetic genes, ipnA and aatA. Deletion of hapB, hapC, and hapE genes, which encode PENR1 complex components, resulted in identical phenotypes characterized by low levels of ipnA and aatA expression as well as a slow-growth phenotype and a reduction in conidiation (74,87,112).…”
Section: Ccaat Binding Protein Complexmentioning
confidence: 99%
“…The A. nidulans CCAAT binding protein complex PENR1 has been reported to regulate both development and penicillin production (74,112). PENR1 positively regulates the expression of two penicillin biosynthetic genes, ipnA and aatA.…”
Section: Ccaat Binding Protein Complexmentioning
confidence: 99%
“…In fact, the orthologuous HAP complex in mammals (CBF) has a wide range of target genes (Maity & de Crombrugghe, 1998). In fungi the HAP complex has been implicated in regulation of genes involved in the catabolism of carbon and nitrogen sources and secondary metabolism (Litzka et al, 1996). It is thus possible that different activator subunits can be associated with the core complex ('domain borrowing'), providing specificity for particular sets of genes.…”
Section: Gln3 Plays a Role As Hap-complex Co-activatormentioning
confidence: 99%
“…Sucrose (or glucose) repression of the ipnA (ϭpcbC) gene of A. nidulans is known (10,26,72), but Litzka and coworkers reported that expression of the A. nidulans pcbAB gene using reporter gene fusions was not repressed by the carbon source (53). The basic regulatory mechanisms of carbon and nitrogen regulation were initially believed to be similar in both fungi (28,47).…”
Section: Differences In Carbon Catabolite Regulation and Ph Control Omentioning
confidence: 99%